The impact of tax preferences on the investment attractiveness of bonds for retail investors: The case of Russia - Natalia B. Boldyreva; Liudmila G. Reshetnikova; Elena A. Tarkhanova; Zhanna V. Pisarenko; Svetlana A. Kalayda (Journal of Risk and Financial Management, 2020)
The impact of tax incentives on the investment attractiveness of bonds for retail investors is assessed in the article. The paper presents a comparative empirical analysis of investment attractiveness of Russian bonds and bank deposits for domestic retail investors. We identify investment preferences of retail investors in Russia, analyze investment characteristics of deposits in Russian banks and a variety of bonds available for retail investors. Given the tax benefits of the recently introduced Individual Investment Account, we show that the real yield of investment in government bonds is over eight times higher than the yield of bank deposits. Despite higher risks of investing in bonds, we conclude that government bonds taking into account the tax benefits of the Individual Investment Account could be a realistic alternative to bank deposits for Russian retail investors.
Keywords: 330; banking; financial market; investment decisions; investor protection; risk